2021
DOI: 10.1101/2021.05.10.443359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pioneer transcription factors are associated with the modulation of DNA methylation patterns across cancers

Abstract: Methylation of cytosines on DNA is a prominent modification associated with gene expression regulation. Aberrant DNA methylation patterns have recurrently been linked to dysregulation of the regulatory program in cancer cells. To shed light on the underlying molecular mechanism driving this process, we hypothesized that aberrant methylation patterns could be controlled by the binding of specific transcription factors (TFs) across cancer types. By combining DNA methylation arrays and gene expression data with T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 107 publications
1
2
0
Order By: Relevance
“…Based on our computational predictions, we chose to validate experimentally if binding of two candidate TFs FOXA1 and GATA3, were indeed upstream of DNA methylation changes. Previous studies also observed a local DNA hypo-methylation at FOXA1 binding sites [40,41], which was recently confirmed by Lemma et al [39]. Both TFs have been described as pioneer TFs as they can bind and open closed chromatin [42].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Based on our computational predictions, we chose to validate experimentally if binding of two candidate TFs FOXA1 and GATA3, were indeed upstream of DNA methylation changes. Previous studies also observed a local DNA hypo-methylation at FOXA1 binding sites [40,41], which was recently confirmed by Lemma et al [39]. Both TFs have been described as pioneer TFs as they can bind and open closed chromatin [42].…”
Section: Discussionsupporting
confidence: 57%
“…Although Rhie et al did not integrate TF motif or binding sites, FOXA1 and GATA3 in BRCA were identified in their study [15]. The method from Fleischer et al had also associated FOXA1 and GATA3 with changes in DNA methylation patterns in BRCA [16], which they confirmed in a recent study across 19 cancer types [39].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the group of TFs known as pioneer transcription factors can bind densely closed inactive chromatin, leading to the recruitment of remodeling complexes, changing chromatin con guration, and epigenetic modi cations, ultimately facilitating the binding of other transcription factors (Mayran and Drouin, 2018;Zaret and Carroll, 2011). Noteworthy, aberrant methylation patterns are found in numerous disease conditions, including cancer (Detilleux et al, 2022;Lemma et al, 2022). It is now established that DNA methylation is an epigenetic modi cation crucial for the recruitment and/or selection of transcription factors (TF) within the chromatin, ultimately resulting to profound alteration of transcriptomic pro les.…”
Section: Introductionmentioning
confidence: 99%